Awareness and Knowledge About RefractiveSurgery Among Medical Students in Baghdad: Doi: 10.36351/pjo.v40i2.1726 - Suzan Amana Rattan; Muayad Ridha , Ruba; Qhatan Majeed , Batool; Zaki Hussien, Zahraa; Ali Abdullah , Nabaa (Pakistan Journal of Ophthalmology, 2024)
Purpose: Refractive error represents a common eye disorder that can significantly impact an individual's visual function and overall well-being. There are several methods of correcting refractive errors and objective of this study was to assess the awareness of refractive surgery and the preferred methods of refractive error correction among medical students in Baghdad. Study Design: Cross sectional survey. Place and Duration of Study: University of Baghdad Al-Kindy College of Medicinefrom November 2022 to March 2023. Methods: Medical students from six Baghdad medical colleges with total sample size of 350 were included. Students who had undergone refractive surgeries and fifth and sixth year medical students were also excluded. Level of knowledge was categorized as; <50% (0-5) poor knowledge, 50-70% (6-8) moderate knowledge and >70% (9-12) good knowledge. Results: Among the students with refractive errors, 82% had knowledge about their refractive error. Forty percent had myopia, 12% had astigmatism, 15 % had myopia and astigmatism, 10% had hyperopia, 5% had hyperopia and astigmatism. Among them 57.8% were not willing to undergo refractive surgery due to fear of complications. Forty eight percent had poor knowledge,43.1% had moderate and only 8.26% had a good knowledge of refractive surgeries. The majority preferred eyeglasses (82.6%) followed by both eyeglasses and contact lenses. Conclusion: Students had good awareness about refractive surgery but their familiarity and knowledge about it remained poor because of complications. An overwhelming majority of students still preferred spectacles as the method for vision correction.